Efektivitas Edukasi Komik dan Leaflet terhadap Peningkatan Pengetahuan Orangtua Siswa Sekolah Dasar Mengenai PHBS untuk Pencegahan Penularan Virus Covid-19 - Fabiola Shania Alicia Rustiarini (2021)
Background: COVID-19 is currently a major health problem worldwide. Indonesia is one of the countries affected and is in the 21st position with the most positive cases of Covid in the world. Children who are exposed to the Covid-19 virus usually only cause mild symptoms or even cause no symptoms. This makes children a source of spreading the virus without realizing it. Therefore, education on how to prevent the transmission of Covid-19 (Clean and Healthy Living Behavior) is important to prevent children from being exposed to the Covid-19 virus and becoming a source of infection without realizing it. Objective: To determine the effect of comic education and leaflets on increasing the knowledge of parents of elementary school students about PHBS for preventing the transmission of the Covid-19 virus. Methods: This study used a quasy experimental design with a desaign pre-posttest group design involving 68 parents of grade V students who were selected by cluster random sampling. Knowledge data collection is carried out online. Results: There were differences in respondents' knowledge of the effect of comics education media use (p = 0,) and leaflets (p = 0,). Conclusion: There is an effect of nutrition education through comics and leaflets on knowledge about Clean and Healthy Living Behaviors in parents of elementary school students as an effort to prevent the transmission of the Covid-19 virus.